Public Administration Agendas in the Light of New Public Management: A Written Testimony of Reform Initiatives of an Asian Country: NPM Led Reforms in Public Administration - Nikhil Chandra Shil; Anup Chowdhury (Journal of Public Administration and Government, 2023)
This paper presents a conceptual discussion of New Public Management (NPM) driven reform initiatives in public administration. NPM is a management philosophy used since the 1980s by many governments, particularly developed countries, namely the US, UK, Australia and New Zealand, to modernize the way the public sector works. The developing countries have also embarked on the path of transformation since the 1990s. Bangladesh has also witnessed various public administration reform initiatives since independence, but is gaining momentum after 1990s with significant use of NPM modalities to make the public sector more responsive and results-oriented. This paper brings the success stories from the global market, and critiques the case of Bangladesh in its administrative reform initiatives through the lens of the NPM. The analysis is based on various secondary sources such as policy papers, research articles, archive material, etc. Based on the discussions, the paper concludes with some recommendations.